Vinde a mim os pequeninos : história da educação de crianças desamparadas na Instituição Educativa Espírita (1947-1992 - Santana, Rosemeire Siqueira (2016)
This study aimed to understand the implementation process of the Spiritualist School “Casa do Pequenino”, which encompasses the Escola Amélie Boudet and Lar Meimei, and school culture and educational practices developed in these institutions.Besides the educational procedure used for these children and the role of the institution in the field of education poor chilhhood, some concepts were used, among them, the school culture. The time frame of this research is the period 1947-1992; it was delimited from the year of conception of a spiritualist institution dedicated to education and the year of closing of the activities of the Lar Meimei. The theoretical and methodological basis of this research are contained in the presuppositions of the History New and have the basis researches related to the History of Education, Education of Orphans and School Culture, produced by researchers such as: Clarice Nunes, Dominique Julia and Irma Rizzini. For a better understanding of the theme was used concepts of “representation” and “appropriation” of Roger Chartier (2002), and “memory” of Pollack (1992). During the research, several institutions were visited, including: Arquivo Público do Estado de Sergipe, Arquivo da Escola Espírita “Casa do Pequenino”, Arquivo da União Espírita de Sergipe, Arquivo da Federação Espírita Sergipana e do Instituto Histórico e Geográfico de Sergipe. Were used and analyzed various sources such as: Registrations Books Registrations, Diaries, Laws and Decrees of the State of Sergipe, Intern Rules, Newspapers, Minutes, Oral Reports, as well as professional literature. The history of assistance to poor children in Brazil went through several formats, believing that the charity would contribute through these philanthropic educational institutions for the formation of poor children. Likewise, representatives of the Spiritualist Union in Sergipe, embraced the desire to present the underprivileged children the opportunity to build a different "way" to their lives. In Brazil, the emergence of spiritualists schools occurred in the early twentieth. The followers of doctrine saw the "charity" as essential for the improvement of man, especially with regard to the care of orphans and poor children. Thus, based on the possibility of receiving these children, his followers were attentive to educate people, care for, instruct and present opportunities for growth. During 1947, the followers of the Spiritualist Doctrine in Sergipe, occupied themselves realization works of social protection, such as building of schools and orphanages. Thus, they aspired to contribute to education of the poor from the religious precepts of spiritualism.